Porous Fibers: Spinning Angora Rabbit Wool-Like Porous Fibers from a Non-Equilibrated Gelatin/Water/2-Propanol Mixture (Adv. Funct. Mater. 13/2014) - Stoessel, Philipp R.; Grass, Robert N.; Sánchez-Ferrer, Antoni; Fuhrer, Roland; Schweizer, Thomas; Mezzenga, Raffaele; Stark, Wendelin J. (Advanced functional materials, 2014)
The luxury angora rabbit fiber stands out from other animal hair. Its porous structure combines exceptional insulation and comfortable wear. On page 1831, W. J. Stark and co‐workers present a method by which a structurally equivalent protein filament can be synthesized in a continuous process. Raw material slaughterhouse waste‐derived gelatin is utilized, adding value to this low‐cost biopolymer.